IJTIHAD SCIENTIFIC DALAM HUKUM ISLAM (Refleksi Metodologis Penemuan Hukum Islam) - Muhibbuddin, Muhammad (IAIN Tulungagung, 2015)
This article is an attempt to offer an idea in integrating religions and scienceto answer the problems in the contemporary Islamic law. In this matter, thewriter proposes to employ an experiment as to answer the problem of theminimum age to get married according to Marriage Act in Indonesia. Thefindings reveal that the use of scientific effort can be used as to integratereligion and science by doing experiments and holistic interpretation of anyreligious text.Kata kunci: Ijtihad Scientific, Relasi Sains dan Hukum Islam, RefleksiMetodologis